2011
DOI: 10.1111/j.1365-2044.2011.06891.x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the utility of the Intubation Difficulty Scale for use with indirect laryngoscopes

Abstract: SummaryThe purpose of this study was to determine whether the Intubation Difficulty Scale is meaningful when used with indirect laryngoscopes. Data were analysed from previously published clinical trials from our group that compared the indirect laryngoscopes with the Macintosh laryngoscope. For each laryngoscope type, the Intubation Difficulty Scale score obtained for each tracheal intubation was correlated with data for duration of the intubation attempt and with the user rated difficulty of the intubation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
10
0
1
Order By: Relevance
“…Comme critère de jugement secondaire, nous avons utilisé une échelle de difficulté d'intubation, qui est largement utilisée et qui a été validée pour les laryngoscopies directes. Son utilité pour l'évaluation des laryngoscopes indirects n'est pas encore établie, 36 toutefois une corrélation positive est retrouvée entre l'échelle de difficulté d'intubation et un score subjectif (échelle visuelle analogique) dans la plupart des études. 27,36 Dans notre étude l'Airtraq et le X-Lite ont permis de réduire le temps d'intubation par rapport au laryngoscope standard dans la chirurgie thyroïdienne.…”
Section: Discussionunclassified
“…Comme critère de jugement secondaire, nous avons utilisé une échelle de difficulté d'intubation, qui est largement utilisée et qui a été validée pour les laryngoscopies directes. Son utilité pour l'évaluation des laryngoscopes indirects n'est pas encore établie, 36 toutefois une corrélation positive est retrouvée entre l'échelle de difficulté d'intubation et un score subjectif (échelle visuelle analogique) dans la plupart des études. 27,36 Dans notre étude l'Airtraq et le X-Lite ont permis de réduire le temps d'intubation par rapport au laryngoscope standard dans la chirurgie thyroïdienne.…”
Section: Discussionunclassified
“…However, a study by McElwain et al [47] found that the correlation between the IDS score and both user rated difficulty and the time needed for tracheal intubation was significantly stronger for the Macintosh laryngoscope than for the indirect laryngoscopes studied (GlideScope, Pentax AWS, Airtraq). These findings led the authors to conclude that the IDS "performs less well with indirect laryngoscopes than with the Macintosh laryngoscope" and that clinicians should use "caution with the use of this score with indirect laryngoscopes.…”
Section: Prediction Of Difficult Gs Intubationmentioning
confidence: 91%
“…However, a retrospective study by McElwain has raised concerns about the validity of the IDS with VLS [13]. The most important outcome parameter for VLS or any guided intubation devices is the success rate.…”
Section: Methodsmentioning
confidence: 99%